2018
DOI: 10.21763/tjfmpc.465766
|View full text |Cite
|
Sign up to set email alerts
|

A tobacco use survey among university students focusing on waterpipe use and relationship between first-tried tobacco product and becoming an established smoker

Abstract: Objective: We aimed to describe tobacco use and tobacco related attitudes and perceptions among the Yeditepe University students with a special focus on waterpipe use, and to investigate the relationship between first-tried tobacco product and established smoking. Method: An anonymous questionnaire survey (a cross-sectional study) was conducted in the spring term of the 2014-15 academic year. Study subjects included all four year students (n=354) of the faculties of medicine, pharmacy, dentistry, and health sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The World Health Organization (2017) indicated the smoking prevalence among individuals aged 15 and over as 27.5%. Smoking is more common among university students than in general society (Hossain et al, 2017;Sezer et al, 2018;Tucktuck et al, 2018;Vatansev et al, 2019). Vatansev et al (2019) reported the smoking rates as 11.6% among medical faculty students.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (2017) indicated the smoking prevalence among individuals aged 15 and over as 27.5%. Smoking is more common among university students than in general society (Hossain et al, 2017;Sezer et al, 2018;Tucktuck et al, 2018;Vatansev et al, 2019). Vatansev et al (2019) reported the smoking rates as 11.6% among medical faculty students.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is more common among university students than in general society. According to the results of a study conducted with university students, 53.5% of males and 29.7% of females smoked 4,5 5 reported the smoking rates as 11.6% among medical faculty students and 50% among communication faculty students.…”
Section: Introductionmentioning
confidence: 99%